16‐channel bow tie antenna transceiver array for cardiac MR at 7.0 tesla. Issue 6 (17th July 2015) - Oezerdem, Celal; Winter, Lukas; Graessl, Andreas; Paul, Katharina; Els, Antje; Weinberger, Oliver; Rieger, Jan; Kuehne, Andre; Dieringer, Matthias; Hezel, Fabian; Voit, Dirk; Frahm, Jens; et al.
Abstract : Purpose: To design, evaluate, and apply a bow tie antenna transceiver radiofrequency (RF) coil array tailored for cardiac MRI at 7.0 Tesla (T). Methods: The radiofrequency (RF) coil array comprises 16 building blocks each containing a bow tie shaped λ/2‐dipole antenna. Numerical simulations were used for transmission field homogenization and RF safety validation. RF characteristics were examined in a phantom study. The array's suitability for high spatial resolution two‐dimensional (2D) CINE imaging and for real time imaging of the heart was examined in a volunteer study. Results: The arrays transmission fields and RF characteristics are suitable for cardiac MRI at 7.0T. The coil performance afforded a spatial resolution as good as (0.8 × 0.8 × 2.5) mm 3 for segmented 2D CINE MRI at 7.0T which is by a factor of 12 superior versus standardized protocols used in clinical practice at 1.5T. The proposed transceiver array supports 1D acceleration factors of up to R = 6 without impairing image quality significantly. Conclusion: The 16‐channel bow tie antenna transceiver array supports accelerated and high spatial resolution cardiac MRI. The array is compatible with multichannel transmission and provides a technological basis for future clinical assessment of parallel transmission techniques at 7.0 Tesla. Magn Reson Med 75:2553–2565, 2016. © 2015 Wiley Periodicals, Inc.